Viral Content and Social Change in Rural Communities - Nuriza Dora; Tsuchiya Takeshi; Nasution, Nasution (Universitas Negeri Surabaya, 2025)
The rise of viral content on social media has transformed social behaviour and value systems, particularly in rural Indonesian communities exposed to unfiltered digital information. This study examines how viral content shapes traditional values and intergenerational relations. Using a qualitative case study approach, data were gathered through interviews, observations, and document analysis involving content creators, housewives, civil servants, and rural youth. The analysis included data reduction, classification, and interpretation. Findings reveal that viral content exerts both positive and negative effects. While some content promotes education and creativity, much of it normalises unethical behaviour and fosters individualism. Content creators often prioritize popularity over ethics, parents and teachers struggle to monitor youth exposure, and younger generations increasingly perceive traditional values as obsolete. This shift weakens communal norms such as cooperation, respect, and collective responsibility. The study concludes that viral content accelerates cultural transformation and erodes moral education in rural settings. Therefore, strengthening media literacy, digital ethics, and cultural revitalisation programs is crucial to balancing modernisation with the preservation of local wisdom and social cohesion in the digital era.